A Case of Severe Mitral Valve Regurgitation in a Patient with Leadless Pacemaker - Srikala R. Gumireddy; Minako Katayama; Hari P. Chaliki (Case Reports in Cardiology)
An 85-year-old man with cardiac history notable for atrial fibrillation diagnosed 10 years ago which was being treated with atenolol and warfarin presented to our institution with persistent atrial fibrillation. His echocardiogram showed ejection fraction (EF) of 56%, no regional wall motion abnormalities, mild mitral and pulmonary regurgitation, and trivial tricuspid regurgitation. Despite this treatment, he had recurrent episodes of paroxysmal symptomatic atrial fibrillation with a rapid rate requiring multiple emergency department visits and hospital admissions. Given difficulty to control the rate, he underwent atrioventricular (AV) nodal ablation and leadless pacemaker insertion. Fifteen days after the procedure, he was found to have a severe mitral regurgitation murmur.